Morphological evaluation of mutant lines of torch ginger (Etlingera elatior) - Abd Wahid, Norfaizah (2014)
Mutant lines of Etlingeraelatior have been established and early detection of mutation has been performed using random amplification of polymorphic DNA (RAPD) markers in earlier study in the laboratory. This study evaluated the morphological characteristics of the mutant lines after 8 weeks of acclimatization. The mutant lines which were earlier multiplied and rooted under in vitro condition were transferred into potting medium consisting of soil: sand: peat moss (1:1:1) and acclimatized in a misting chamber and the plants were watered daily and monitored to ensure healthy and good growth until 8 weeks. Each mutant line represented a treatment. Each treatment containedsix replications, with one plantlet per replication. Parameters recorded after 8 weeks of acclimatization were the mean height of plant (cm), mean number of leaves produced per plant, mean length of leaves, and mean width of leaves. Data were analyzed using the Analysis of Variance (ANOVA) (GLM procedure) and Duncan Multiple Range Test (DMRT) for mean separation. The survived plantlets showed different general growth rate and some showed abnormal morphological characteristics. Mutant line L2 exhibited among the highest mean plant height, mean length of leaves, mean number of leaves, and mean width of leaves after 8 weeks of acclimatization. Meanwhile, mutant line L4 produced among the shortest plant with some abnormality on the leaves and among the lowest number of leaves per plant, mean length of leaves, as well as mean width of leaves.